'Speaking nearby': Reflections on the conversations with Erika Tan. (1st July 2022) - Lua, Lenette; Zhang, Huanzhi
How can we reconfigure the concept of Chinese art when the term Chinese extends beyond geographical specificity? From May to December 2021, researchers Lenette Lua and Huanzhi Zhang initiated a series of informal, open conversations with London-based Singaporean artist Erika Tan over Zoom. In these conversations, Tan shared the thinking process behind her moving image Journeys of Remembrance ([1993] 2008) and project The 'Forgotten' Weaver (2016‐19), as well as her involvement in calling for Arts Council England to defund Centre for Chinese Contemporary Arts in Manchester for its White occupancy. By reflecting on the conversations with Tan and her propositions, the conversation unveils the struggle in grasping the exponentiality of Chineseness and seeks to unravel Chineseness as a fluctuating silhouette of continuous constructions and deconstructions that defies definition.